Trends in extraction and purification methods of Lignans in plant-derived foods - Yu-tong Yang; Yuan Zhang; Yu Bian; Juan Zhu; Xue-song Feng (Food Chemistry: X)
Lignans are widely used as dietary supplements within health foods. However, excess addition of lignans can induce adverse reactions, therefore, it is necessary to develop rapid, effective, economical, and environmentally friendly extraction and purification methods to enhance lignan extraction efficiency. Recently, the advancement of sample pretreatment has been primarily directed towards the application of novel extraction solvents (e.g., supramolecular solvents) in dispersive liquid-liquid microextraction, the miniaturization of solid-phase extraction, the utilization of innovative adsorbent materials in dispersive solid-phase microextraction and matrix-assisted solid-phase extraction, and the employment of subcritical water extraction technology. Up to now, no systematic review has encompassed these advancements. Consequently, this review provides a comprehensive overview of the extraction and purification methods of lignans from plant-derived foods since 2017, with a particular focus on the application of microextraction technologies and new materials. It also analyzes the advantages and disadvantages of these methods and discusses their future developing trends.